PENGARUH PENGGUNAAN METODE ROLE PLAYING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP BUSTANUL MAKMUR GENTENG - Ainur Rofiq; Imam Mashuri (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2021)
This thesis examines the effect of the role playing method on student learning outcomes, which is motivated by the learning outcomes that there are still some students who score below the minimum completeness criteria and the previous role playing learning methods have never been used by teachers or educators at Bustanul Makmur Junior High School. This type of research is a Pre-Experimental Design with a One Group Pretest-Posttest research design using a quantitative approach. The population in this study were students of SMP Bustanul Makmur Genteng class VIII with a total of 184 students. The sample in this study was 76 of 184 students. The sampling technique uses a random cluster sampling. To determine the effect of student learning outcomes, the results of written tests were used in the form of multiple choice with a total of 20 items and were carried out using two categories, namely the pretest and the posttest which were then analyzed using the prerequisite test and hypothesis testing. Statistical techniques Paired Sample T-Test. Based on the results of the analysis, it is known that the data on student learning outcomes by applying the role playing method in PAI class VIII A at SMP Bustanul Makmur Genteng, this value it can be seen that the value of t count> t table value (11.925> 2.026), the significance level of 5% (0.05) is greater than sig. (2-tailed) of 0.000 (0.05> 0.000), Which means that there is an influence in the application of the role playing method on the learning outcomes of class VIII A at SMP Bustanul Makmur Genteng. The correlation value of the T test is 0.777 which means it is in the strong or high category.